Clinical efficiency of self-etching one-step and two-step adhesives in NCCL: A systematic review and meta-analysis - De-Assis, C. P.P.; Lemos, C. A.A.; Gomes, J. M.L. [UNESP]; Vasconcelos, B. C.E.; Moraes, S. L.D.; Braz, R.; Pellizzer, E. P. [UNESP] (Operative Dentistry, 2020)
Objective: A systematic review and meta-analyses were performed to evaluate whether onestep self-etching (1SSE) adhesive systems are as effective as two-step self-etching (2SSE) adhesives in noncarious cervical lesion (NCCL) restorations. Methods: This systematic review was conducted according to the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) and recorded in the PROSPERO (CRD42018096747). Electronic systematic searches were conducted in the following databases: PubMed/MEDLINE, Scopus, and Cochrane Library for published articles. Only randomized clinical trials that compared 1SSE with 2SSE adhesives systems were selected. The outcomes were retention, postoperative sensitivity, secondary caries, color match, marginal discoloration, marginal adaptation, and anatomical form. Results: The searches resulted in 476 studies. After applying the eligibility criteria, five randomized controlled trials were selected in which 822 restorations in NCCLs were distributed in 237 patients. The results showed no statistical difference between 1SSE and 2SSE in relation to retention (p=0.23; relative risk [RR]=1.55; 95% confidence interval [CI]=0.76, 3.19), postoperative sensitivity (p=0.50; RR=3.00; 95% CI=0.13, 70.64), Secondary caries (p=0.63; RR=0.68; 95% CI=0.14, 3.31), color match (p=0.41; RR=0.64; 95% CI=0.23, 1.83), marginal discoloration (p=0.93; RR=1.02; 95% CI=0.65, 1.61), and anatomical form (p=0.56; RR=1.38; 95% CI=0.46, 4.13). However there was statistical difference in relation to marginal adaptation (p=0.01; RR=1.95; 95% CI=1.14, 3.34). Conclusion: This systematic review with metaanalysis revealed that both 1SSE and 2SSE adhesive systems have comparable clinical effectiveness in a follow-up period of 12 to 24 months, except in relation to marginal adaptation.